Studi Eksperimental Perpindahan Panas pada Pengering Sepatu Berbasis Rak Datar - Putrawan, I Made Agus; Adiaksa, I Made Anom; Wibawa, I Wayan Suma; Adi, I Ketut (Journal of Applied Mechanical Engineering and Green Technology, 2026)
Shoe drying is a crucial process for maintaining hygiene and extending the lifespan of footwear, especially in high-humidity environments. This study aims to experimentally investigate the heat transfer characteristics of a flat-rack-based shoe dryer. The system is designed with electric heating elements and a horizontal rack configuration to promote uniform heat distribution. Key observed parameters include inlet air temperature, shoe surface temperature, drying time, and moisture content reduction. Measurements were conducted at multiple rack levels to evaluate vertical and horizontal temperature distribution. The results indicate that forced convection is the dominant heat transfer mechanism, with relatively uniform temperature distribution observed in the middle racks, while the top and bottom racks experienced temperature deviations. The heat transfer by radiation generated by the shoe dryer is 5.41 J/s, and the convective heat transfer is 238.8 J/s. The moisture content loss increases with drying time, indicating that 90 minutes is the optimal drying duration among the tested variations. This study provides a foundation for the development of more energy-efficient shoe drying systems and highlights the potential for integrating alternative heat sources such as solar energy.